-3x+7x-5=4(x-1)-11

Simple and best practice solution for -3x+7x-5=4(x-1)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+7x-5=4(x-1)-11 equation:



-3x+7x-5=4(x-1)-11
We move all terms to the left:
-3x+7x-5-(4(x-1)-11)=0
We add all the numbers together, and all the variables
4x-(4(x-1)-11)-5=0
We calculate terms in parentheses: -(4(x-1)-11), so:
4(x-1)-11
We multiply parentheses
4x-4-11
We add all the numbers together, and all the variables
4x-15
Back to the equation:
-(4x-15)
We get rid of parentheses
4x-4x+15-5=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation

See similar equations:

| 22-s/3=s | | (4^(x+2)-4^(x+1)=96 | | 2x-3(2-3x)=3(x-3)-13 | | 17=3(y+1)+8 | | -26=2+4u | | (3x-1)^2=-4 | | (2x+1)^2-(16)=0 | | t−14= 4 | | 26=5u-4 | | -u+177=25 | | 2s−s=13 | | 5(x-10)=10(x+3) | | -4+5n=9n | | -u+179=246 | | 5q+10q+-9=6 | | 7x-10=7x-4 | | 0.04(56)+0.16x=0.08(x+56) | | 169=279-v | | 5r+2r−4=17 | | 4q+9=5q+19 | | -y+285=162 | | 10m-12=11m+13 | | -10=x/2-4 | | 3/x-12=28 | | x+3/5x-2=x/x+1 | | -28=4-8v | | Va=0.6 | | 6(10)+-5-4=x | | x=-2(-5) | | 6(1-2y)+y-4+11(1-2y)+2=180 | | x/3+5=75 | | 20.5=-15.5=(-3.6x)+1.8 |

Equations solver categories